Polyethylene and silica gel mixed material, preparation method and composite optical cable silicon core tube

By constructing a composite system of high-density polyethylene and ethylene-siloxane copolymer elastomer, combining maleic anhydride grafting reaction and carbon chain length differentiated paraffin, the flexibility and weather resistance problems of polyethylene materials in complex environments are solved, and the elastic recovery, interface stability and long-term service performance of the material are improved.

CN120795443APending Publication Date: 2025-10-17SHANGHAI BST TUBING

Patent Information

Application Number
CN202510861311.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing polyethylene materials lack flexibility under complex load environments and have limited resistance to stress cracking. Multi-component composite systems also have problems such as poor compatibility, unstable interfaces, and uncontrolled lubricant migration, which affect processing stability and service life.

Method used

By constructing a composite system of high-density polyethylene, ethylene-siloxane copolymer elastomer, maleic anhydride grafted polyolefin elastomer, liquid paraffin and hydroxylated nano-silica, a "hard-soft" interpenetrating network structure is formed. The maleic anhydride grafting reaction is used to construct a stable chemical anchoring interface. Combined with paraffin and nanocellulose crystals with different carbon chain lengths, the dual construction of interfacial stress synergy and functional network is achieved.

Benefits of technology

The elastic recovery ability, strain fracture resistance, interface connection stability and long-term weather resistance of composite materials are improved to meet the needs of engineering applications in complex environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a polyethylene and silica gel mixed material, a preparation method thereof and application of the polyethylene and silica gel mixed material in a composite optical cable silicon core tube. The composite material comprises the following components in parts by weight: high-density polyethylene, an ethylene-siloxane copolymer elastomer, a maleic anhydride grafted polyolefin elastomer, hydroxylated nano silicon dioxide, liquid paraffin, a crystallization nucleating agent, an ultraviolet light absorber, an auxiliary stabilizer, a processing aid and color master batch. The liquid paraffin is formed by blending dual-molecular-weight paraffin with different carbon chain lengths, and part of the liquid paraffin is grafted and modified by polybutylene so as to enhance the anchoring capacity of the lubricating phase; in addition, nano cellulose crystals grafted by a PEG-PCL (Polyethylene Glycol-Polycaprolactone) block copolymer are introduced, so that the dimensional stability and the interface structure integrity of the material are synergistically enhanced. The composite material has excellent low friction, thermal oxidation stability, creep resistance and ultraviolet aging resistance, and is suitable for preparation of a high-performance composite optical cable silicon core tube.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer composite materials, and particularly relates to a polyethylene and silica gel mixed material, a preparation method and a composite optical cable silica core tube. BACKGROUND

[0002] Polyethylene is widely used in the fields of communication optical cable, pipe material, packaging and the like due to its excellent mechanical properties, chemical stability and processability. However, the pure polyethylene material has problems of insufficient flexibility, limited stress cracking resistance and the like, and is prone to structural fatigue and performance degradation under complex load environment or long-term service condition. In order to improve the overall performance, an elastomer, inorganic filler or lubricant is usually used for blending modification, but there are problems of poor compatibility, unstable interface, uncontrolled migration of lubricant and the like in the multi-component composite system, which affect the process stability and service life.

[0003] In recent years, siloxane elastomers are gradually introduced into the polyethylene matrix to improve the flexibility and environmental adaptability due to their excellent flexibility, low glass transition temperature and weather resistance. At the same time, nano fillers such as hydroxylated silicon dioxide are also used to improve the mechanical properties and thermal stability of the material. However, in the multi-phase composite system composed of polyethylene, siloxane elastomer and inorganic components, how to build a stable interface structure, realize the synergistic effect between components and improve the comprehensive performance of the composite material on the basis of maintaining the processability is still an important technical difficulty in current engineering application research. Especially in the application scenarios such as silica core tube for optical cable which have extremely high requirements for interface lubricity, dimensional stability and long-term aging resistance, the existing material system still has certain performance bottlenecks. SUMMARY

[0004] In view of the deficiencies in the prior art, the present application aims to provide a polyethylene and silica gel mixed material, a preparation method and a composite optical cable silica core tube.

[0005] A polyethylene and silica gel mixed material includes the following components by weight:

[0006] High-density polyethylene: 50-65 parts;

[0007] Ethylene-siloxane copolymer elastomer: 8-12 parts;

[0008] Maleic anhydride grafted polyolefin elastomer: 4-8 parts;

[0009] Hydroxylated nano-silicon dioxide: 1-2 parts;

[0010] Paraffin wax: 1.5-2.5 parts;

[0011] Beta-type crystalline nucleating agent: 0.1-0.3 parts;

[0012] UV absorber: 0.1-0.3 parts;

[0013] Auxiliary stabilizer: 0.2-0.4 parts;

[0014] Processing aid: 0.5-1.5 parts;

[0015] Color masterbatch: 10-25 parts;

[0016] The paraffin is a liquid paraffin with a carbon chain length of C20-C40.

[0017] The present application solves the problems of interfacial stress concentration, composition instability and difficulty in unifying synergistic properties in a multi-phase polymer system by rationally constructing a composite system composed of high-density polyethylene, ethylene-siloxane copolymer elastomer, maleic anhydride grafted polyolefin elastomer, liquid paraffin and hydroxylated nano-silicon dioxide.

[0018] The ethylene-siloxane copolymer elastomer has flexible siloxane segments and ethylene segments, which disperse in the HDPE semi-crystalline matrix to form a continuous phase or a discrete phase, and interpenetrate with the rigid HDPE under melt blending conditions to construct a "hard-soft" network structure, effectively improving the elastic recovery capacity and strain fracture resistance of the composite material.

[0019] The anhydride groups in the maleic anhydride grafted polyolefin elastomer can form hydrogen bonds or esterification reactions with the hydroxyl groups on the surface of the siloxane elastomer or hydroxylated nano-SiO2 during processing, forming a stable chemical anchoring interface, enhancing the compatibility between polar and non-polar components in the composite system, and inhibiting the risk of interfacial debonding and phase separation.

[0020] At the same time, the MAH-g-POE constructs a flexible bridging dissipative structure between HDPE and the silica elastomer, which can undergo segment slipping and deformation during loading, dissipate interfacial stress fluctuations, and delay crack initiation and propagation.

[0021] The introduction of paraffin promotes the aggregation of polar anhydride groups to the interface through the melting wetting effect, constructing a low-shear- viscosity lubricating layer in the composite system, further reducing the interfacial viscous force, improving the blending uniformity and processing fluidity. In addition, paraffin molecules can be embedded between MAH-g-POE segments during melt blending, and form interchain entanglement or crystalline nest structure under the crystallization induction during cooling, realizing the interfacial migration and locking of the lubricating phase, preventing late precipitation or aggregation, and thus ensuring the structural stability and lubrication durability of the composite system interface.

[0022] The above multi-component synergistic effect realizes the dual construction paths of interfacial stress synergy and functional network cohesion on the macro level, effectively improving the low friction, high flexibility and strong weather resistance of the composite material, and meeting the engineering application requirements for long-term use in complex environments.

[0023] Further, the ethylene-siloxane copolymer elastomer is linear structure, and the unit mole percentage of the siloxane main chain is 20-40%.

[0024] Further, the grafting rate of the maleic anhydride in the maleic anhydride grafted polyolefin elastomer is 0.5-1.5wt%, and the molecular weight range is 50000-300000.

[0025] The ethylene-siloxane copolymer elastomer is linear structure, and the unit mole percentage of the siloxane main chain is controlled to be 20-40%, which is beneficial to forming a uniformly distributed elastic phase in the high-density polyethylene matrix, the siloxane segment provides excellent flexibility and low glass transition temperature, so that the material still has good toughness and resilience at low temperature; at the same time, the proper proportion of ethylene segments can improve the compatibility and melt blending reactivity in the polyethylene matrix, thereby enhancing the interface penetration and physical crosslinking between the two phases, stabilizing the construction of the "hard-soft" interpenetrating network structure, and further enhancing the flexibility and dynamic stress response ability of the overall material.

[0026] The grafting rate of the maleic anhydride in the maleic anhydride grafted polyolefin elastomer is controlled to be 0.5-1.5wt%, which can ensure that a sufficient number of anhydride groups form hydrogen bonds or ester bonds with the hydroxyl groups on the surface of nano-SiO2 or siloxane elastomer, realizing effective interface chemical anchoring, and the excessive grafting avoids the reaction supersaturation causing interface embrittlement or the dramatic increase of the system viscosity. The molecular weight range of the grafted elastomer is set to be 50000-300000, which can form stable interchain entanglement and energy absorption structure on the basis of ensuring that the molecular chain has sufficient flexibility and mobility; at the same time, this molecular weight range helps the MAH-g-POE to form a continuous flexible bridging structure in the interface layer, further improving the micro stress dissipation capacity and the stable locking effect of the lubricating layer, thereby realizing the further improvement of the stress synergy, component interface stability and long-term service performance in the composite system.

[0027] Further, the liquid paraffin is blended by two paraffins with different molecular weights, which include:

[0028] a low molecular weight paraffin with a carbon chain length of C20-C25, and

[0029] a high molecular weight paraffin with a carbon chain length of C35-C40,

[0030] The two are blended in a mass ratio of (1-3):(1-2).

[0031] Liquid paraffin wax is blended from low-molecular-weight paraffin wax (C20-C25) and high-molecular-weight paraffin wax (C35-C40) in a mass ratio of (1-3):(1-2), forming a hierarchical "short-chain-long-chain" lubricating structure. Due to their low molecular weight and high fluidity, the short-chain components preferentially migrate to the interface between polyethylene and silicone elastomer during the initial melting stage of processing, rapidly forming a lubricating layer. This significantly reduces interfacial shear resistance and melt viscosity, improving material flow processing performance and blending uniformity. The long-chain components, on the other hand, slowly migrate to the interface during the subsequent cooling stage. Leveraging their higher chain length and adhesion, they form a dense and stable coating at the interface, filling the structural gaps in the initial lubricating layer and enhancing its continuity and structural integrity.

[0032] This dynamic division of labor mechanism, with short chains providing "early lubrication" and long chains providing "later anchoring," effectively broadens the paraffin wax's interfacial migration window during processing, allowing for greater time adjustment margin and spatial expansion capabilities for the formation and locking of the lubricating phase. It also optimizes the efficiency of the interface's coordinated transformation from a dynamic lubrication state to a static anchoring state, ensuring the lubricating layer retains structural stability and migration resistance after dynamic stress loading. This not only improves the composite material's initial processing adaptability and interfacial dispersion, but also ensures its long-term low-friction performance and interfacial structural durability during its service life, further enhancing the overall material system's flexibility, wear resistance, and weather resistance.

[0033] Furthermore, 10% to 30% of the low molecular weight paraffin and polybutene are pre-grafted and modified.

[0034] The grafted paraffin wax, formed by grafting a small amount of low-molecular-weight paraffin wax (carbon chain length C20-C25) onto polybutene, maintains the good fluidity and wetting properties of the original paraffin wax while introducing an olefin backbone structure that can undergo segmental entanglement or van der Waals interactions with ethylene-siloxane copolymer elastomer (POE), significantly enhancing its directional adsorption capacity and local retention stability within the POE phase domain. During dynamic melt blending, this structure migrates to the interface with the low-molecular-weight paraffin wax and forms a lubricating layer. At the same time, due to the POE affinity of the grafted segment, it achieves "adhesion anchoring" within the POE region, effectively inhibiting its free precipitation during high-temperature melt or service, and improving the structural retention of the paraffin lubricating layer under local high-temperature stress fields.

[0035] In addition, the graft modification of 10% to 30% proportion makes a certain proportion of "semi-immobilized lubricating factors" exist in the interface. Such molecules have a certain degree of freedom of movement and can still respond to stress release demand at the micro level to maintain the strain adaptability of the lubrication channel. At the same time, due to the structural anchoring effect, it significantly prolongs the effective period of the interface lubrication state and reduces the risk of lubrication phase separation induced by thermal aging. Therefore, this modification strategy is particularly suitable for polymer composite systems that need to serve in high-temperature, high-shear or high-load environments for a long time, further improving the thermal stability, lubrication durability and overall service reliability of the material.

[0036] Further, the component further comprises 0.2 to 1 parts of nanocellulose crystals surface grafted with polyethylene glycol-poly-caprolactone block copolymer.

[0037] Further, the polyethylene glycol-poly-caprolactone block copolymer is synthesized by ring-opening polymerization, wherein the number average molecular weight of polyethylene glycol is controlled to be 2000 to 5000, and the mass ratio of polyethylene glycol to poly-caprolactone is 3:1.

[0038] The nanocellulose crystals are surface grafted with PEG-PCL block copolymer, which is prepared by ring-opening polymerization, and the number average molecular weight of polyethylene glycol is controlled to be 2000 to 5000, and the mass ratio of PEG to PCL is 3:1. After the above treatment, the CNC surface has both hydrophilic hydroxyl groups and flexible segments, which can realize multiple interface coupling. On the one hand, the carboxyl groups on the surface of CNC cross-link with the anhydride groups in MAH-g-POE to form an interface connection structure of "chemical bond + physical entanglement", which enhances the fixation and distribution stability of CNC in the elastic phase; on the other hand, the hydroxyl groups on the surface of CNC can form a hydrogen bond network with hydroxylated SiO2, which expands the stress transmission path and constructs micro multi-adhesion sites.

[0039] At the same time, CNC has high longitudinal rigidity and linear rod-like structure, which shows a certain induction nucleation effect in the crystallization process of HDPE, promotes the local orientation arrangement of crystal grains along the CNC direction, and forms a "rod-like directional" crystal structure, thereby improving the anti-creep performance and size retention ability of the material under long-term load. This microstructure improves the deformation resistance and structural density of the composite material, effectively controlling the thermal expansion behavior.

[0040] In addition, the PEG-PCL modified CNC has strong interfacial activity and polyethylene matrix wettability, which enhances its dispersion uniformity in the non-polar PE phase and avoids the defect structure of aggregation; part of the surface modification segment can also reversibly adsorb liquid paraffin, adjust the spatial distribution of the lubricant in the interface region, and inhibit the excessive migration or uncontrolled diffusion of paraffin, further strengthening the local stability of the lubrication layer.

[0041] In summary, the CNC synergistic construction path not only extends the interface interaction link at the molecular scale, but also forms a directional fibrous skeleton network at the microstructure, which is an enhancement form that cannot be achieved by conventional polyethylene systems. This ordered micro-fiber network gives the composite material significantly better thermal stability, dimensional stability, crack resistance, and interface synergistic stability than traditional systems, further promoting the structural level evolution of the overall composite system from "multiphase blending" to "synergistic integration", and realizing the unified improvement of flexibility, stability and interface function.

[0042] A method for preparing a polyethylene and silica gel mixed material, comprising the following steps:

[0043] S1: mixing maleic anhydride grafted polyolefin elastomer and liquid paraffin in proportion at 70-90°C for 10-20 minutes, stirring speed 300-600 rpm, cooling for standby;

[0044] S2: ultrasonic dispersion of surface hydroxylated nano-silica in ethanol, drying for standby;

[0045] S3: dry mixing high-density polyethylene, β-type crystalline nucleating agent, ultraviolet light absorber, auxiliary stabilizer, processing aid and color master batch in proportion at a temperature range of 40-60°C, mixing time 3-10 minutes;

[0046] S4: mixing ethylene-siloxane copolymer elastomer with the mixture obtained in step S1 at 80-100°C for 10-15 minutes;

[0047] S5: using a twin-screw extruder, setting the following temperature zones for feeding:

[0048] The first feeding zone temperature is 160-170°C, the feeding is the mixture of step S2, and the screw rotation speed is controlled at 80-120 rpm;

[0049] The second feeding zone temperature is 180-190°C, the feeding is the mixture obtained in step S3, and the screw rotation speed is increased to 150-200 rpm;

[0050] The third feeding zone temperature is 200-205°C, and the mixture obtained in step S4 is added;

[0051] The fourth zone is set as a vacuum devolatilization section;

[0052] S5: incubation and shearing at a temperature of 185-195°C for 5 minutes;

[0053] S6: controlling the discharge port temperature to 170°C, low shear extrusion molding at 30-50 rpm, and cooling and granulation.

[0054] Further, the third feeding area of the step S5 proportionally adds the nanocellulose crystal surface grafted with polyethylene glycol-poly (ε-caprolactone) block copolymer, and the shear rate of the third feeding area stirring section is 80-100 rpm, and the mixing time is 3 minutes.

[0055] Further, a heat pressure maintaining section is arranged at the end of the twin-screw extrusion system, the temperature of the pressure maintaining section is 190-195℃, and the residence time is 3-6 minutes.

[0056] In the material preparation process, first, paraffin and maleic anhydride grafted polyolefin elastomer (MAH-g-POE) are premixed at 70-90℃ to construct a “composite interfacial additive masterbatch” with preliminary wettability and polarity activity, which helps to form a synergistic migration unit in subsequent processing, ensuring that paraffin and MAH-g-POE are co-dispersed in the interfacial region, synergistically migrate, and through interchain entanglement, realize “migration-locking” dual-function integration under cooling induction, effectively inhibiting paraffin migration and phase separation in the later stage.

[0057] By controlling the temperature and screw speed of each feeding area of the twin screw in sections, the injection of key structural components is realized in time and in sections, ensuring that each phase completes the melting diffusion and interface positioning under the most suitable thermal conditions. The first feeding area has a lower temperature, which is conducive to maintaining the surface structure of nanometer SiO2 and ensuring the activity of its hydroxyl groups; the second feeding area injects HDPE main material, which, in combination with high-speed shearing, promotes the uniform plasticization of the main phase and the dispersion of nucleating agents and other additives; the temperature of the third feeding area is increased to 200-205℃, which makes the ethylene-siloxane copolymer elastomer and the dispersed interfacial additive masterbatch form an interpenetrating network under high shear and fully contact with the main phase interface, realizing the structure introduction of the flexible phase and the positioning of the interfacial lubricating layer.

[0058] Further, nanocellulose crystals (CNC) modified by PEG-PCL grafting are introduced into the third feeding area, and the shear rate and mixing time are controlled to realize anhydride crosslinking with MAH-g-POE, hydrogen bonding with nanometer SiO2, and directional induction in the HDPE crystallization process, cooperatively constructing an ordered microfiber network and a multi-point interface communication path, enabling the interface to have multi-scale reinforcement capability and structural hierarchy stability.

[0059] Further, by setting a pressure maintaining section (190-195℃, 3-6 minutes), the structure of each component in the final form is further improved, the lubricant distribution is more balanced, the interface interaction chain is more fully entangled, and the structure is prevented from being loose or the performance from being uneven due to insufficient reaction or unpositioned lubricant.

[0060] An application of a polyethylene and silica gel mixed material in preparing a composite optical cable silica core tube.

[0061] Compared with the prior art, the beneficial effects of the present application mainly lie in the following aspects:

[0062] (1) The present application forms a "hard-soft" network structure by melt blending ethylene-siloxane copolymer elastomer and high-density polyethylene, which enhances the elastic recovery and fracture resistance of the material. At the same time, maleic anhydride grafted polyolefin elastomer is introduced as an interface bridging phase, and the anhydride group and inorganic hydroxyl or siloxane segment undergo hydrogen bonding or esterification reaction to build a stable chemical anchoring interface, greatly improving the compatibility between polar and non-polar components, effectively preventing phase separation and debonding, and strengthening the interface connection stability.

[0063] (2) The use of double-molecular-weight paraffin with different carbon chain lengths allows short-chain paraffin to migrate to the interface first during the initial stage of processing, reducing the melt viscosity and improving the processing fluidity; long-chain paraffin is slowly anchored in the interface region during the cooling stage, enhancing the structural integrity of the lubricating layer. Further modification of low-molecular-weight paraffin by polybutylene grafting allows it to have both flow lubrication and interface anchoring properties, forming a semi-fixed lubricating factor in the flexible phase, effectively inhibiting the free migration and precipitation of paraffin in high-temperature environments, and improving the retention and durability of the lubricating layer under complex service conditions.

[0064] (3) Surface-grafted polyethylene glycol-poly-caprolactone block copolymer nanocellulose crystals (CNC) have high rigidity and multifunctional interface activity, and can induce rod-like orientation and arrangement of crystal grains during blending with HDPE, forming a rigid microfiber skeleton structure that significantly improves the dimensional stability and creep resistance of the material. At the same time, the surface functional groups of CNC can form a multi-interface connection network with MAH-g-POE and hydroxylated SiO2, enhancing the structural hierarchical synergistic effect; the flexible surface segments also have paraffin adsorption capacity, which can regulate the spatial distribution of lubricants, prevent local enrichment or excessive migration of paraffin, and further improve the uniformity and stability of the interface lubricating layer.

[0065] (4) The preparation method constructs an interface additive masterbatch by premixing paraffin and MAH-g-POE, and injects each functional component in different zones during twin-screw extrusion, combining temperature and shear rate gradient control to realize time-sharing synergistic construction between different phases. The third feeding zone is set to high temperature and high shear conditions to guide the embedding of the flexible phase into the main chain network; the end heat pressure section further promotes the locking of the lubricating phase, the fullness of the crosslinking reaction, and the stability of the crystal region, ensuring the uniformity and long-term service stability of the composite material. DETAILED DESCRIPTION

[0066] The present application will be described in detail below with reference to examples.

[0067] Example 1

[0068] This embodiment discloses a polyethylene and silica gel mixed material, which comprises the following components in parts by weight:

[0069] High-density polyethylene: 50 parts;

[0070] Ethylene-siloxane copolymer elastomer: 8 parts;

[0071] Maleic anhydride grafted polyolefin elastomer: 4 parts;

[0072] Hydroxylated nano-silica: 1 part;

[0073] Paraffin: 1.5 parts;

[0074] β-type crystal nucleating agent: 0.1 part;

[0075] UV absorber: 0.1 part;

[0076] Auxiliary stabilizer: 0.2 parts;

[0077] Processing aid: 0.5 parts;

[0078] Masterbatch: 10 parts.

[0079] The high-density polyethylene adopts Borealis HE3490-LS HDPE material produced by Borealis Chemical Company.

[0080] The ethylene-siloxane copolymer elastomer was Wacker produced by Wacker Chemie AG. Material of PE50S08 model.

[0081] ExxonMobil maleic anhydride grafted polyolefin elastomer produced by DuPont TM Material for model N493.

[0082] The average particle size of hydroxylated nano-silica is 20nm and the specific surface area is 300m 2 / g of hydroxylated nano-silica particles.

[0083] Paraffin wax is mainly liquid paraffin wax with a carbon chain length of C20.

[0084] The β-type crystal nucleating agent used is TMB-5 nucleating agent.

[0085] UV absorber uses 327 Benzotriazole UV absorber.

[0086] The auxiliary stabilizer adopts the model 1010 hindered phenolic antioxidant and model The compound system is obtained by compounding the phosphite auxiliary antioxidant of 168 in a mass ratio of 1:2.

[0087] The processing aid is a low-density polyethylene wax additive of model AC-6A produced by Honeywell.

[0088] The masterbatch is produced by Cabot Corporation of the United States. PE White MB White masterbatch of PE2653.

[0089] This embodiment also discloses a method for preparing a polyethylene and silica gel mixed material, comprising the following steps:

[0090] S1: Mix the maleic anhydride-grafted polyolefin elastomer and liquid paraffin wax in appropriate proportions in a sealed stirred reactor. Heat and stir at 70°C for 10 minutes at 300 rpm to allow the liquid paraffin wax to fully wet and penetrate the elastomer, forming a uniform plasticized mixture. After the reaction, cool to room temperature and set aside.

[0091] S2: Weigh 1 wt% of hydroxylated nano-SiO2 particles and add them to 95% anhydrous ethanol at a mass ratio of 1:20. Ultrasonic dispersion is performed at 300 W for 15 minutes to ensure thorough dispersion of the nanoparticles. The ethanol is then removed by hot air drying at 80°C or rotary evaporation under reduced pressure. Finally, the nano-SiO2 is dried to a constant weight and set aside.

[0092] S3: Dry mix high-density polyethylene, β-type crystal nucleating agent, ultraviolet light absorber, auxiliary stabilizer, processing aid and masterbatch in proportion at a temperature range of 40°C for 3 minutes to ensure uniform distribution.

[0093] S4: Add the ethylene-siloxane copolymer elastomer and the maleic anhydride elastomer / paraffin wax mixture obtained in step S1 into a mixer in proportion, stir at 80° C. for 10 minutes to ensure that the two are evenly blended, and cool to below 40° C. after discharge for use.

[0094] S5: Use a twin-screw extruder and set the feeding temperature to the following zones:

[0095] The temperature of the first feeding zone is 160°C, the feed is the mixture of step S2, and the screw speed is controlled at 80-120 rpm;

[0096] The temperature of the second feeding zone is 180°C, the feed is the mixture obtained in step S3, and the screw speed is increased to 150-200 rpm;

[0097] The temperature of the third feeding zone is 200°C, and the mixture obtained in step S4 is added;

[0098] The fourth zone is set as a vacuum devolatilization section, a vacuum degree of -0.08 MPa is maintained, and water, low molecular residue and ethanol residue are removed for 5 minutes;

[0099] S6: After the material enters the last-stage shear zone, the temperature is maintained at 190°C, and shearing is maintained for 5 minutes to enhance the interfacial adhesion between layers and the dispersibility of the modified particles in the polymer matrix;

[0100] S7: The temperature of the discharge port is controlled to be 170°C, low-shear extrusion is performed at 30 rpm, and cooling granulation is performed. The cooling water bath temperature is controlled to be 20°C. The composite master batch with a particle size of 3 mm is obtained by passing through a traction granulator, and is packaged for use.

[0101] Example 2

[0102] The present embodiment discloses a polyethylene and silica gel mixed material, which comprises the following components by weight:

[0103] High-density polyethylene: 65 parts;

[0104] Ethylene-siloxane copolymer elastomer: 12 parts;

[0105] Maleic anhydride grafted polyolefin elastomer: 8 parts;

[0106] Hydroxylated nano-silicon dioxide: 2 parts;

[0107] Paraffin wax: 2.5 parts;

[0108] Beta-type crystalline nucleating agent: 0.3 parts;

[0109] Ultraviolet light absorber: 0.3 parts;

[0110] Auxiliary stabilizer: 0.4 parts;

[0111] Processing aid: 1.5 parts;

[0112] Color master batch: 25 parts.

[0113] The high-density polyethylene adopts a HDPE material of Borealis HE3490-LS type produced by the North European Chemical Company.

[0114] The ethylene-siloxane copolymer elastomer adopts a material of Wacker PE50S08 type produced by Wacker Chemie AG Company.

[0115] The maleic anhydride grafted polyolefin elastomer adopts a material of N493 type produced by DuPont Company. TM ExxonMobil.

[0116] ​The hydroxylated nano-silica has an average particle size of 30 nm, a specific surface area of 200 m 2 / g, and a hydroxyl content of 5.0 wt%.

[0117] The liquid paraffin has a carbon chain length of C40.

[0118] The β-type crystalline nucleating agent is TMB-5 nucleating agent.

[0119] The ultraviolet light absorber is 327 benzotriazole ultraviolet absorber.

[0120] The auxiliary stabilizer is a compound system of a hindered phenol antioxidant with a model number of 1010 and a phosphite auxiliary antioxidant with a model number of 168 in a mass ratio of 1:2.

[0121] The processing aid is a low-density polyethylene wax additive with a model number of AC-6A produced by Honeywell.

[0122] The color master batch is a white color master batch with a model number of PE White MB PE2653 produced by Cabot.

[0123] The embodiment also discloses a preparation method of the polyethylene and silica gel mixed material, comprising the following steps:

[0124] S1: after the maleic anhydride grafted polyolefin elastomer and the liquid paraffin are mixed in proportion, they are placed in a closed stirring reaction kettle, heated at 90°C and stirred for 20 minutes, the stirring speed is controlled to be 600 rpm, the liquid paraffin is fully wetted and penetrated into the elastomer, and a uniform plasticized mixture is formed. After the reaction is completed, it is cooled to room temperature and is ready for use.

[0125] S2: the hydroxylated nano-SiO2 particles are weighed, 2 wt% of which is added to 95% concentrated anhydrous ethanol, and ultrasonic dispersion treatment is performed in a mass ratio of 1:20, the ultrasonic power is 500 W, and the time is 30 minutes, so that the nano-particles are fully dispersed. Then, 90°C hot air drying or reduced pressure rotary evaporation method is used to remove the ethanol, and finally the nano-SiO2 is dried to a constant weight and is ready for use.

[0126] S3: the high-density polyethylene, the β-type crystalline nucleating agent, the ultraviolet light absorber, the auxiliary stabilizer, the processing aid and the color master batch are dry-mixed in proportion at a temperature range of 60°C, and the mixing time is 10 minutes, so that they are uniformly distributed.

[0127] S4: Put the ethylene-siloxane copolymer elastomer and the mixture of maleic anhydride elastomer / paraffin wax obtained in step S1 into a mixer in proportion, stir at 100°C for 15 minutes to ensure uniform fusion, and cool to below 40°C after discharging for standby.

[0128] S5: Use a double-screw extruder and set the following temperature zones for feeding:

[0129] The first feeding zone temperature is 170°C, the feeding is the mixture of step S2, and the screw speed is controlled at 120 rpm;

[0130] The second feeding zone temperature is 190°C, the feeding is the mixture obtained in step S3, and the screw speed is increased to 200 rpm;

[0131] The third feeding zone temperature is 205°C, and the mixture obtained in step S4 is added;

[0132] The fourth zone is set as a vacuum devolatilization section, maintaining a vacuum degree of -0.09 MPa for 10 minutes to remove moisture, low molecular residue and ethanol residue;

[0133] S6: After the material enters the final shear zone, it is kept at 190°C for 5 minutes to enhance the interfacial adhesion and the dispersibility of the modified particles in the polymer matrix;

[0134] S7: Control the discharge port temperature to be 170°C, extrude at a low shear of 50 rpm, and cool and granulate. The cooling water bath temperature is controlled at 25°C. After cutting by a traction granulator, composite master batch with a particle size of 5 mm is obtained and packaged for use.

[0135] Example 3

[0136] This example discloses a polyethylene and silica gel mixed material, which comprises the following components by weight:

[0137] High-density polyethylene: 57.5 parts;

[0138] Ethylene-siloxane copolymer elastomer: 10 parts;

[0139] Maleic anhydride grafted polyolefin elastomer: 6 parts;

[0140] Hydroxylated nano-silicon dioxide: 1.5 parts;

[0141] Paraffin wax: 2 parts;

[0142] Beta-type crystalline nucleating agent: 0.2 parts;

[0143] Ultraviolet light absorber: 0.2 parts;

[0144] Auxiliary stabilizer: 0.3 parts;

[0145] Processing aid: 1 part;

[0146] Color masterbatch: 17.5 parts.

[0147] High-density polyethylene adopts Borealis HE3490-LS type HDPE material produced by North European Chemical Company.

[0148] Ethylene-siloxane copolymer elastomer adopts Wacker PE50S08 type material produced by Wacker Chemie AG Company.

[0149] Maleic anhydride grafted polyolefin elastomer adopts ExxonMobil TM N493 type material produced by DuPont Company.

[0150] Hydroxylated nano-silica adopts hydroxylated nano-silica particles with an average particle size of 10 nm and a specific surface area of 300 m 2 / g.

[0151] Paraffin wax is liquid paraffin wax with a carbon chain length of C30.

[0152] Beta-type crystalline nucleating agent adopts TMB-5 nucleating agent.

[0153] Ultraviolet light absorber adopts 327 benzotriazole ultraviolet absorber.

[0154] Auxiliary stabilizer adopts a compounded system obtained by compounding a hindered phenol antioxidant with a type number of 1010 and a phosphite auxiliary antioxidant with a type number of 168 in a mass ratio of 1:2.

[0155] Processing aid adopts low-density polyethylene wax additive with a type number of AC-6A produced by Honeywell Company.

[0156] Color masterbatch adopts white color masterbatch with a type number of PE White MB PE2653 produced by American Cabot Company.

[0157] The embodiment also discloses a preparation method of the polyethylene and silica gel mixed material, comprising the following steps:

[0158] S1: after the maleic anhydride grafted polyolefin elastomer and the liquid paraffin wax are mixed in proportion, they are placed in a closed stirring reaction kettle, heated at 80 DEG C and stirred for 15 minutes, the stirring speed is controlled to be 450 rpm, the liquid paraffin wax is fully wetted and penetrated into the elastomer, and a uniform plasticized mixture is formed. After the reaction is completed, it is cooled to room temperature and is ready for use.

[0159] S2: Weigh the hydroxylated nano-SiO2 particles and add them to 95% concentration of anhydrous ethanol at a ratio of 1.5wt%, and perform ultrasonic dispersion treatment at a mass ratio of 1:20, ultrasonic power 400W, and time 22.5 minutes, to ensure that the nanoparticles are fully dispersed. Then use hot air drying at 85°C or a rotary evaporation method under reduced pressure to remove the ethanol, and finally dry the nano-SiO2 to a constant weight for later use.

[0160] S3: Dry mix the high-density polyethylene, β-type crystalline nucleating agent, ultraviolet light absorber, auxiliary stabilizer, processing aid, and color masterbatch in proportion at a temperature range of 50°C, with a mixing time of 6.5 minutes to ensure uniform distribution.

[0161] S4: Put the ethylene-siloxane copolymer elastomer and the maleic anhydride elastomer / paraffin wax mixture obtained in step S1 into a mixer in proportion, and stir at 90°C for 12.5 minutes to ensure uniform fusion of the two, and cool to below 40°C after discharging for later use.

[0162] S5: Use a twin-screw extruder and set the following temperature zones for feeding:

[0163] The first feeding zone temperature is 165°C, and the feeding is the mixture of step S2, with the screw speed controlled at 80-120rpm;

[0164] The second feeding zone temperature is 185°C, and the feeding is the mixture obtained in step S3, with the screw speed increased to 150-200rpm;

[0165] The third feeding zone temperature is 202°C, and the feeding is the mixture obtained in step S4;

[0166] The fourth zone is set as a vacuum devolatilization section, maintaining a vacuum degree of -0.085MPa for 7.5 minutes to remove moisture, low molecular residue, and ethanol residue;

[0167] S6: After the material enters the final shear zone, maintain the temperature at 190°C for 5 minutes of shearing to enhance the interfacial adhesion and the dispersibility of the modified particles in the polymer matrix;

[0168] S7: Control the discharge port temperature to be 170°C, and extrude at a low shear of 40rpm for cooling and granulation. The cooling water bath temperature is controlled at 22.5°C. After cutting by a traction granulator, composite masterbatch particles with a particle size of 4mm are obtained, which are packaged for later use.

[0169] Example 4

[0170] The difference between this example and Example 3 is that the ethylene-siloxane copolymer elastomer is linear, and the siloxane backbone unit mole percentage is 30%.

[0171] Example 5

[0172] The difference between this embodiment and embodiment 4 is that the maleic anhydride grafting rate in the maleic anhydride grafted polyolefin elastomer is 1wt%, and the molecular weight range is 200000.

[0173] Embodiment 6

[0174] The difference between this embodiment and embodiment 5 is that the liquid paraffin is blended from two paraffins with different molecular weights, including low molecular weight paraffin with carbon chain length C20 and high molecular weight paraffin with carbon chain length C40, and the two are blended in a mass ratio of 3:2.

[0175] Embodiment 7

[0176] The difference between this embodiment and embodiment 6 is that the low molecular weight paraffin with a content of 30% is pre-grafted with polybutene, and the specific steps are as follows:

[0177] Step 1: Raw material ratio and premixing

[0178] The liquid paraffin with carbon chain length C20 and polybutene (molecular weight 800) are weighed and premixed in a mass ratio of 4:1. Maleic anhydride is added as a grafting monomer, and the addition amount is 1.5wt% of the total mass of the paraffin-polybutene mixture. Dicumyl peroxide (DCP) is added as an initiator, and the addition amount is 0.3wt%.

[0179] Step 2: Melt reaction grafting

[0180] The above mixture is put into a high-shear melt reactor with inert atmosphere protection, heated to 160℃ under nitrogen protection, and the reaction temperature is maintained and melt reaction is carried out under stirring at 350rpm, and the reaction time is 30 minutes. In this process, maleic anhydride reacts with polybutene under the initiation of peroxide, and paraffin acts as a solvent to participate in dispersion and plasticization.

[0181] Step 3: Cooling, granulation and stabilization

[0182] After the reaction is completed, the temperature is lowered to below 90℃, the material is poured out, quickly cooled by liquid nitrogen and crushed to obtain a grafted paraffin-polybutene blend granules. Then it is placed in a vacuum drying oven at 80℃ for 4 hours to remove residual monomers and low molecular weight byproducts, and finally the modified product is obtained.

[0183] Embodiment 8

[0184] The difference between this embodiment and embodiment 7 is that the component of the polyethylene and silica gel mixed material also includes 0.5 parts of nanocellulose crystals grafted with polyethylene glycol-poly-caprolactone block copolymer on the surface.

[0185] The specific preparation steps of the nanocellulose crystal grafted with polyethylene glycol-poly-caprolactone block copolymer are as follows:

[0186] Step 1: Pretreatment of nanocellulose crystal

[0187] 1.1 Take commercially available nanocellulose crystal (CNC) prepared by sulfuric acid method, with a particle size of about 200 nm and a solid content controlled at 2 wt%, and disperse in deionized water;

[0188] 1.2 Adjust the pH to 5, and use ultrasonic dispersion at 300 W for 20 minutes to make it fully dispersed;

[0189] 1.3 Prepare powder-like CNC through freeze-drying or spray-drying, and dry in a vacuum drying oven at 80°C to constant weight.

[0190] Step 2: Pre-synthesis of PEG-PCL block copolymer

[0191] 2.1 Prepare the block copolymer by ring-opening polymerization: mix monomethoxypolyethylene glycol (mPEG, molecular weight 2000) and caprolactone in a mass ratio of 3:1 in dry tetrahydrofuran under a dry nitrogen atmosphere, and add stannous octoate as a catalyst (the addition amount is 0.5 wt% of the total monomer mass);

[0192] 2.2 After reacting at 75°C for 24 hours, precipitate, filter, and dry to obtain the product;

[0193] 2.3 Dissolve the product obtained in step 2.2 in anhydrous dichloromethane, add succinic anhydride and 4-dimethylaminopyridine (DMAP) in a molar ratio of 1:1.2, and react at room temperature under a nitrogen atmosphere for 12 hours; after the reaction is completed, the reaction liquid is precipitated, centrifuged, washed with water, and vacuum dried to obtain a PEG-PCL block copolymer with carboxyl groups introduced at the end.

[0194] Step 3: Grafting reaction

[0195] 3.1 Take 1 part of dry CNC powder and 3 parts of mPEG-b-PCL copolymer with carboxyl groups introduced at the end, and disperse them in a dichloromethane / dimethylformamide (volume ratio 1:1) mixed solvent;

[0196] 3.2 Add N,N'-dicyclohexyl carbodiimide and 4-dimethylaminopyridine as esterification reaction promoters, with the addition amount of DCC being 1.2 times the molar amount of CNC hydroxyl groups and the addition amount of DMAP being 0.1 times;

[0197] 3.3 React at room temperature for 8 hours, and then heat to 40°C for 12 hours to form an ester bond grafting structure between the PEG-PCL copolymer and the surface hydroxyl groups of CNC;

[0198] 3.4 After the reaction is completed, free copolymer and by-products are removed by washing (ethanol, deionized water repeatedly 3 times) through centrifugation, and finally freeze-dried to obtain CNC powder with PEG-PCL block copolymer grafted on the surface.

[0199] The nanocellulose crystals grafted with polyethylene glycol-poly-caprolactone block copolymer are added in proportion in the third feeding zone of step S5, and the shear rate of the stirring section of the third feeding zone is 100 rpm, and the mixing time is 3 minutes.

[0200] Example 9

[0201] The difference between this example and example 8 is that a heat holding section is arranged at the end of the twin-screw extrusion system, the temperature of the holding section is 190℃, and the residence time is 5 minutes.

[0202] Comparative Example 1

[0203] The difference between this comparative example and example 1 is that the paraffin wax is not included in the components of the polyethylene and silica gel mixed material.

[0204] The preparation method of the polyethylene and silica gel mixed material of this comparative example is as follows:

[0205] S1: Weigh the hydroxylated nano-SiO2 particles, add 1wt% to 95% concentration of anhydrous ethanol, and ultrasonic dispersion treatment with a mass ratio of 1:20, ultrasonic power 300W, time 15 minutes. Then use 80℃ hot air drying or rotary evaporation under reduced pressure to remove ethanol, dry to constant weight for standby.

[0206] S2: Dry mix the high-density polyethylene, β-type crystalline nucleating agent, ultraviolet light absorber, auxiliary stabilizer, processing aid and color master batch in proportion at 40℃ for 3 minutes.

[0207] S3: Put the ethylene-siloxane copolymer elastomer and maleic anhydride grafted polyolefin elastomer directly into the mixer, stir at 80℃ for 10 minutes, and cool to below 40℃ for standby.

[0208] S4: Use a twin-screw extruder, set the temperature zone as follows:

[0209] The first feeding zone temperature is 160℃, the feeding is the mixture of step S1, and the screw rotation speed is controlled at 80-120rpm;

[0210] The second feeding zone temperature is 180℃, the feeding is the mixture obtained in step S2, and the screw rotation speed is increased to 150-200rpm;

[0211] The third feeding zone temperature is 200℃, and the mixture obtained in step S3 is added;

[0212] The fourth zone is set as a vacuum devolatilization section, and the vacuum degree is maintained at -0.08 MPa for 5 minutes to remove moisture, low molecular residue and ethanol residue;

[0213] S5: After the material enters the final section shear zone, it is kept at 190°C for 5 minutes of shear;

[0214] S6: The temperature of the discharge port is controlled at 170°C, and the material is extruded and formed at a low shear of 30 rpm, and then cooled and granulated. The cooling water bath temperature is controlled at 20°C. The composite material master batch with a particle size of 3 mm is obtained by cutting through a traction granulator, and is packaged for use.

[0215] Comparative Example 2

[0216] The difference between this comparative example and Example 1 is that the polyethylene and silica gel mixed material does not contain a maleic anhydride grafted polyolefin elastomer in the components.

[0217] The difference between the preparation method of the polyethylene and silica gel mixed material of this comparative example and Example 1 is that the S1 step is adjusted to directly preheat the liquid paraffin to 70°C for standby, and the blending process with the elastomer is omitted. The S4 step is adjusted to directly mix the ethylene-siloxane copolymer elastomer with the 70°C preheated liquid paraffin, and stir at 80°C for 10 minutes to preliminarily wet the surface of the elastomer with the paraffin. Cool to below 40°C for standby. The other steps are the same as in Example 1.

[0218] Comparative Example 3

[0219] The difference between this comparative example and Example 1 is that the polyethylene and silica gel mixed material does not contain paraffin and a maleic anhydride grafted polyolefin elastomer in the components.

[0220] The difference between the preparation method of the polyethylene and silica gel mixed material of this comparative example and Example 1 is that the S1 step is omitted, and the S4 step is adjusted to only put the ethylene-siloxane copolymer elastomer into the mixer, stir at 80°C for 10 minutes to obtain a premix after softening, and cool to below 40°C for standby. The other steps are the same as in Example 1.

[0221] Comparative Example 4

[0222] The difference between this comparative example and Example 8 is that the mass ratio of monomethoxypolyethylene glycol to caprolactone is 1:4 in the pre-synthesis step of the PEG-PCL block copolymer.

[0223] The preparation method of this comparative example is the same as that of Example 8.

[0224] Detection method

[0225] 1. Dynamic friction coefficient test at high temperature according to the standard basis of GB / T 10006-2021 "Determination of the coefficient of friction of plastics films and sheets", specifically setting the platform temperature to 190℃ on the friction coefficient tester, loading 5N normal load, moving rate 100mm / min, testing the dynamic friction coefficient of the sample at high temperature above the glass transition temperature, recording the change of friction coefficient after 10min (initial friction coefficient μ0; friction coefficient after 10min μ1; μ change ratio μ1 / μ0 (lubricating layer stability reflection))

[0226] The test results are shown in Table 1 below.

[0227] Table 1

[0228] Sample No. initial μ0 Steady state μ1 μ change ratio Example 1 0.15 0.22 1.47 Example 2 0.12 0.18 1.5 Example 3 0.11 0.17 1.55 Example 4 0.1 0.15 1.5 Example 5 0.09 0.14 1.56 Example 6 0.08 0.1 1.25 Example 7 0.08 0.09 1.13 Example 8 0.07 0.09 1.29 Example 9 0.07 0.08 1.14 Comparative Example 1 0.22 0.35 1.59 Comparative Example 2 0.18 0.29 1.61 Comparative Example 3 0.24 0.39 1.63 Comparative Example 4 0.17 0.27 1.59

[0229] From the above test results, it can be seen that the initial friction coefficient and the friction coefficient after 10min of Examples 1-9 are lower than those of Comparative Examples 1-3, indicating that the lubricating effect of the composite material of the examples is better. And the double molecular weight paraffin structure, the grafted modified paraffin and the PEG-PCL grafted CNC all help to reduce the friction coefficient. Although the initial dynamic friction coefficient of Comparative Example 4 is also low, it is difficult to achieve effective fixation and interface anchoring of the lubricant, and its apparent low friction behavior is difficult to maintain.

[0230] 2. Thermogravimetric analysis (TGA): The sample was heated under nitrogen atmosphere (temperature range: 30-700℃, heating rate 10℃ / min), and the 5% thermal weight loss temperature (T5%) and the maximum weight loss rate temperature (Tp) were recorded.

[0231] 3. Oxidation induction time (OIT): According to the standard of GB / T 19466.6-2009 "Plastics - Differential scanning calorimetry (DSC) - Part 6: Determination of oxidation induction time (isothermal OIT) and oxidation induction temperature (dynamic OIT)", under oxygen atmosphere, the temperature was set to 210℃, and the time required for the start of oxidation was recorded.

[0232] The test results of thermogravimetric analysis and oxidation induction time are shown in Table 2 below.

[0233] Table 2

[0234] Sample No. T5%(℃) Tp (°C) OIT (min) Example 1 275 365 13.2 Example 2 280 370 14.5 Example 3 282 372 15 Example 4 283 373 15.3 Example 5 285 375 16.2 Example 6 288 378 17.5 Example 7 292 380 18.8 Example 8 295 382 19.5 Example 9 297 383 20 Comparative Example 1 260 350 10.2 Comparative Example 2 265 352 11 Comparative Example 3 258 348 9.8 Comparative Example 4 273 360 12.1

[0235] 4. In the tensile creep mode, a constant tensile stress of 0.5MPa was applied at 60℃ constant temperature environment, the test time was 72 hours, the displacement change with time was recorded, and the maximum creep amount (ε_max) and the recovery rate after 72h (ε_rec) were calculated.

[0236] The test results are shown in Table 3 below.

[0237] Table 3

[0238] Sample No. Maximum creep strain (%) Recovery rate (%) Example 1 3.6 72 Example 2 3.2 75 Example 3 3.1 76 Example 4 2.9 78 Example 5 2.8 80 Example 6 2.6 83 Example 7 2.3 85 Example 8 1.8 89 Example 9 1.7 91 Comparative Example 1 5.2 60 Comparative Example 2 4.8 62 Comparative Example 3 5.5 58 Comparative Example 4 3.7 70

[0239] 5. Using xenon lamp ultraviolet aging equipment, setting light intensity 0.68 W / m 2 @340 nm, cycle conditions for 8 h ultraviolet + 4 h condensation, aging period 500 h, change of tensile strength and elongation at break before and after testing, calculating performance retention rate.

[0240] The test results are shown in Table 4 below.

[0241] Table 4

[0242] Sample No. Tensile strength retention rate (%) Elongation at break retention rate (%) Example 1 83 78 Example 2 85 80 Example 3 86 81 Example 4 88 82 Example 5 89 84 Example 6 90 86 Example 7 92 88 Example 8 95 90 Example 9 96 91 Comparative Example 1 70 62 Comparative Example 2 73 65 Comparative Example 3 68 60 Comparative Example 4 80 75

[0243] The above only describes the preferred embodiments of the present application, the protection scope of the present application is not limited to the above-mentioned examples, any technical solutions falling within the concept of the present application shall fall within the protection scope of the present application. It should be noted that for ordinary skilled in the art, some improvements and refinements without departing from the principles of the present application, these improvements and refinements should also be considered as the protection scope of the present application.

Claims

1. A polyethylene and silica gel mixed material, characterized in that: The following components are included by weight: High-density polyethylene: 50-65 parts; Ethylene-siloxane copolymer elastomer: 8-12 parts; Maleic anhydride grafted polyolefin elastomer: 4-8 parts; Hydroxylated nano-silica: 1-2 parts; Paraffin: 1.5-2.5 parts; β-type crystal nucleating agent: 0.1-0.3 parts; Ultraviolet light absorber: 0.1-0.3 parts; Auxiliary stabilizer: 0.2-0.4 parts; Processing aids: 0.5-1.5 parts; Masterbatch: 10-25 parts; The paraffin wax is a liquid paraffin wax with a carbon chain length of C20 to C40.

2. The polyethylene and silicone hybrid material according to claim 1, characterized in that: The ethylene-siloxane copolymer elastomer has a linear structure, and the molar percentage of the siloxane main chain unit is 20-40%. The maleic anhydride grafted polyolefin elastomer has a maleic anhydride grafting rate of 0.5-1.5 wt%, and a molecular weight range of 50,000-300,000.

3. The polyethylene and silicone hybrid material according to claim 1, characterized in that: The liquid paraffin is blended by two paraffins with different molecular weights, including: Low molecular weight paraffin wax with carbon chain length of C20 to C25, and High molecular weight paraffin wax with carbon chain length of C35~C40, The mixture is mixed in a mass ratio of (1-3): (1-2).

4. The polyethylene and silicone hybrid material according to claim 3, characterized in that: The low molecular weight paraffin wax with a content of 10% to 30% is pre-grafted and modified with polybutene.

5. The polyethylene and silicone hybrid material according to claim 1, characterized in that: The components also include 0.2 to 1 part of nanometer cellulose crystals with polyethylene glycol-polycaprolactone block copolymer grafted on the surface.

6. The polyethylene and silicone hybrid material according to claim 5, characterized in that: The polyethylene glycol-polycaprolactone block copolymer is synthesized by a ring-opening polymerization method, wherein the number average molecular weight of the polyethylene glycol is controlled to be 2000-5000, and the mass ratio of the polyethylene glycol to the polycaprolactone is 3:

1.

7. A method for preparing a polyethylene and silica gel mixed material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Mixing the maleic anhydride grafted polyolefin elastomer and liquid paraffin in proportion at 70-90° C. for 10-20 minutes at a stirring speed of 300-600 rpm, and cooling for later use; S2: Ultrasonic dispersion of surface hydroxylated nano-silica in ethanol, drying and setting aside; S3: dry-mixing high-density polyethylene, β-type crystal nucleating agent, ultraviolet light absorber, auxiliary stabilizer, processing aid and masterbatch in proportion at a temperature range of 40 to 60° C. for 3 to 10 minutes; S4: mixing the ethylene-siloxane copolymer elastomer with the mixture obtained in step S1 at 80-100° C. for 10-15 minutes; S5: Use a twin-screw extruder and set the feeding temperature to the following zones: The temperature of the first feeding zone is 160-170°C, the feed is the mixture of step S2, and the screw speed is controlled at 80-120 rpm; The temperature of the second feeding zone is 180-190°C, the feed is the mixture obtained in step S3, and the screw speed is increased to 150-200 rpm; The temperature of the third feeding zone is 200-205°C, and the mixture obtained in step S4 is added; The fourth zone is set as the vacuum devolatilization section; S5: Shear at 185–195°C for 5 minutes; S6: Control the outlet temperature to 170°C, perform low shear extrusion molding at 30-50 rpm, and cool and granulate.

8. The polyethylene and silicone hybrid material according to claim 7, characterized in that: The nanocellulose crystals with surface grafted polyethylene glycol-polycaprolactone block copolymer are added to the third feeding zone in step S5 in proportion, and the shear rate of the stirring section in the third feeding zone is 80-100 rpm, and the mixing time is 3 minutes.

9. The polyethylene and silicone hybrid material according to claim 7, characterized in that: A hot holding section is set at the end of the twin-screw extruder system. The holding section temperature is 190-195°C and the residence time is 3-6 minutes.

10. Use of the polyethylene and silicone mixed material according to any one of claims 1 to 6 in preparing a composite optical cable silicon core tube.

Citation Information

Patent Citations

  • A halogen-free flame-retardant polyolefin material, its preparation method and application

    CN102295797A

  • Elastomer sheath material for security cable and preparation method of elastomer sheath material

    CN105801964A

  • Silicon core pipe with good corrosion resistance

    CN106117711A

  • Preparation method of star polymer-based drug carrier material with fluorescence labeling and temperature responsiveness

    CN106589270A

  • Flexible composite lining pipe material

    CN106832524A

Cited By

  • Silicon core pipe and preparation method thereof

    CN121408533A

  • Bimetal steel skeleton polyethylene composite pipe and preparation method thereof

    CN121848754A

  • A bimetallic steel skeleton polyethylene composite pipe and a preparation method thereof

    CN121848754B